Grebeg Penjalin: Komoditifikasi Budaya pada Pemberdayaan Masyarakat Desa Wisata Rotan Trangsan-Sukoharjo - Sarjiyanto Sarjiyanto; Ana Shohibul; Sarwoto Sarwoto; Mulyadi Mulyadi; Suryadari Istiqomah (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of community service in the Trangsan Rattan Tourism Village is to maintain the sustainability of the existence of the rattan industry center. This activity also aims to empower the potentials that are in the location and synergize the socio-economic and cultural potential in an effort to increase empowerment and improve the welfare of citizens in Rotan Tourism Village. The dedication method uses a study-action and participatory approach. Culture as an agent of change through the creation of the cultural event "Grebeg Penjalin" which is held as an annual agenda in the Tangsan Rotan Tourism Village as a cultural commoditization. The results of dedication indicate the commoditization of culture can be an effective attraction. The holding of the Braiding “Grebeg Penjalin" chosen as a cultural event has proven to be able to be an effort to maintain the existence of the Trangsan Rattan Tourism Village which directly contributes to the improvement of the welfare of the people in Trangsan.